2008
DOI: 10.1080/00379271.2008.10697576
|View full text |Cite
|
Sign up to set email alerts
|

Long-term changes in the species composition and distribution of Bombini (Apidae) in Cracow since the mid 1850s

Abstract: Abstract. Current distribution of bumblebee species in Cracow was studied in [2000][2001][2002][2003] in 23 atlas squares. The results were compared with historical data available for last 150 years, including published materials and museum collections. A total 28 bumblebee species were recorded throughout that period. Among them, 11 species are currently threatened in the study area. There were stated three tendencies among the studied bumblebee species. After 1850, 10 species were strongly regressing (withdr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
(8 reference statements)
1
2
0
Order By: Relevance
“…However, as in other studies (e.g. Kosior et al 2008), we showed that some species do not follow the same trends than their hosts. Bombus barbutellus and B. rupestris have a decreasing area whereas their host species, B. hortorum and B. lapidarius, remain among the most abundant and widespread bumblebee species at the national scale (Table 2).…”
Section: Relation Between Species Ecological Traits and Population Changessupporting
confidence: 79%
“…However, as in other studies (e.g. Kosior et al 2008), we showed that some species do not follow the same trends than their hosts. Bombus barbutellus and B. rupestris have a decreasing area whereas their host species, B. hortorum and B. lapidarius, remain among the most abundant and widespread bumblebee species at the national scale (Table 2).…”
Section: Relation Between Species Ecological Traits and Population Changessupporting
confidence: 79%
“…Unlike Oertli et al (2005) in Wallis (Switzerland) and Kosior et al (2008) in Krakow (Poland), we observed a quite constant diversity in Eyne year after year, with 8 to 10 registered species in a 30 specimens sampling (rarefaction Hurlbert index).…”
Section: Yearly Variations In Bumblebee Faunamentioning
confidence: 86%
“…Despite all scenarios showing that the area of this species' occurrence is decreasing due to global warming (Rasmont et al, 2015), B. semenoviellus has been confirmed to be increasing its range in Finland in the 1960s (Elfving, 1965), in Lithuania (Monsevičius, 1993) and in Poland in the 1980s (Pawlikowski, 2008). Currently, it is probably dispersed throughout the whole country but is rarely found Banaszak et al, 2006;Kosior et al, 2008;Pawlikowski, 2008;Banaszak, 2009;Pawlikowski & Pawlikowski, 2012). Its presence has also been confirmed in Germany (Smissen & Rasmont, 2000), Czech Republic (Přidal & Tkalců, 2003), Austria (Streinzer, 2010) and Slovakia (Šima & Smetana, 2012).…”
Section: Methodsmentioning
confidence: 99%